KRITIK ATAS SUNAH SEBAGAI BAGIAN TAFSĪR BI AL-MA’SŪR: MENYOAL OTORITAS SUNAH SEBAGAI ACUAN PENAFSIRAN DALAM TAFSĪR AL-JALĀLAIN - Miski, Miski (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
Tafsīr al-Jalālai, likeTafsīral-Maḥallī andas-Suyūṭī, has not been created from a vacuum, but from a specific context of social reality which is laden with certain ideologies. The questionsthat follow then are how al-Maḥallī and as-Suyūṭīhave put their own ideological genre into Tafsīr al-Jalālain when interpreting al-Qur’an and how this ideological preference in turn brings about theoretical implications for tafsīr bi al-ma’sūr? This paper adopts the perspective of constructionism and that of literature study. The primary data were Tafsīr al-Jalālain, which were analysed by means of intertextuality. The main findings revealed that Sunah in the Tafsīr al- Jalālain have been selected and sorted out in accordance with an ideological genre of Syafii. Building on these observations, we concluded that the existence of SunahNabi which are part of tafsīr bi al-ma‘ṡūr(an-Naql), despite being hailed as the most authoritative interpretation of al-Qur’an, tends to be biased and, therefore, its generalizability should be interpreted with caution. We suggested that there should be a more specific terminology in between al-Qur’an that is interpreted by Nabi himself (i.e., at-Tafsīr an-Nabawī), which tends to be neutral, and al-Qur’an that is interpreted by scholars through the lens of SunahNabi (at-Tafsīr bi as-Sunnah an- Nabawiyyah), which is undoubtedlyvulnerable to the interest of these scholars